2022
DOI: 10.5624/isd.20210172
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension analysis on CBCT scans for detecting low bone mineral density in postmenopausal women

Abstract: Purpose The aim of this study was to compare the fractal dimension (FD) measured at 2 bone sites (second cervical vertebra and mandible) on cone-beam computed tomography (CBCT). The research question was whether FD could serve as an accessory tool to refer postmenopausal women for densitometric analysis. Therefore, the reliability and accuracy of FD were evaluated. Materials and Methods In total, 103 postmenopausal women were evaluated, of whom 52 had normal bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Mathematical analysis of the fractal dimension (FD) was found in three of the included studies, one of which also included the largest number of patients [ 1 ]. The same study showed a significant difference between normal BMD and osteoporosis via mandibular FD analysis, but with low accuracy and reliability (AUC = 0.644, p = 0.008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematical analysis of the fractal dimension (FD) was found in three of the included studies, one of which also included the largest number of patients [ 1 ]. The same study showed a significant difference between normal BMD and osteoporosis via mandibular FD analysis, but with low accuracy and reliability (AUC = 0.644, p = 0.008).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, using fractal dimension (FD) measurements to differentiate between low and normal bone mass showed a statistically significant correlation with the mandibular trabecular bone, but not with the vertebrae in a study published in 2022 [ 1 ], but with low accuracy (area under the curve of 0.64). At the same time, a meta-analysis regarding the use of fractal analysis in dental radiology for osteoporosis detection stated that FD could not be used to identify osteoporotic patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation